Cesarean Scar Defect: A Silent and Growing Complication - Tumenjargal, Amartuvshin; Erdenee, Oyunchimeg; Sharavkhaan, Burmaa; Avirmed, Shiirevnyamba (Central Asian Journal of Medical Sciences, 2023)
No abstract in English